2018
DOI: 10.1016/j.vaccine.2017.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of dengue vaccination in ten endemic countries

Abstract: Following publication of results from two phase-3 clinical trials in 10 countries or territories, endemic countries began licensing the first dengue vaccine in 2015. Using a published mathematical model, we evaluated the cost-effectiveness of dengue vaccination in populations similar to those at the trial sites in those same Latin American and Asian countries. Our main scenarios (30-year horizon, 80% coverage) entailed 3-dose routine vaccinations costing US$20/dose beginning at age 9, potentially supplemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 25 publications
5
43
0
Order By: Relevance
“…There is very little published information regarding the cost of dengue control interventions in Vietnam. It will be important for future studies to evaluate the cost and cost-effectiveness of both the current and novel future interventions 54 , 55 , such as the Dengvaxia ® vaccine 56 , 57 , 58 .…”
Section: Data Gaps and Future Research Needsmentioning
confidence: 99%
“…There is very little published information regarding the cost of dengue control interventions in Vietnam. It will be important for future studies to evaluate the cost and cost-effectiveness of both the current and novel future interventions 54 , 55 , such as the Dengvaxia ® vaccine 56 , 57 , 58 .…”
Section: Data Gaps and Future Research Needsmentioning
confidence: 99%
“…Accordingly, new real-time RT-PCR assays discriminating between wild-type and vaccine strains [ 218 ] or specifically detecting vaccinal strains [ 219 ] were recently published. Molecular YFV diagnostics are further challenged by the application of the new chimeric, live- attenuated DENV vaccine Dengvaxia ® in countries that are endemic for YFV such as Brazil [ 274 , 275 , 276 ]. This vaccine is based on a YFV 17D-backbone expressing the prM and E regions of the four DENV serotypes [ 277 ].…”
Section: How To Mitigate and Manage Yfv Infections?mentioning
confidence: 99%
“…20 In particular, a previous study in 10 endemic countries confirmed that dengue vaccination could be highly cost-effective and a cost-effective intervention in 3 and 7 countries, respectively, according to their gross domestic product (GDP) per-capita values. 21 Despite the fact that dengue vaccine has been licensed in several Asian countries and has proven its cost-effectiveness, a postlicensing monitoring and evaluation (eg, monitoring and registration systems for immunization, reporting, and long-term safety assessments) is still required to be implemented. 22 Considering the results from previous studies, it can be summarized that dengue vaccine in many cases has an ability to reduce the transmission of dengue infection in the community.…”
Section: Introductionmentioning
confidence: 99%